Introduction: Views from the Shoreline: Community, Trade and Religion in Coastal Yorubaland and the Western Niger Delta - Insa Nolte; Olukoya Ogen (Yoruba Studies Review)
This article provides an introduction to the Special Issue entitled, “Views from the Shoreline: Community, trade and religion in coastal Yorubaland and the Western Niger Delta.” Introducing the 19 articles in this Special Issue, which cover the coastal stretch from Ikorodu (near Lagos) to Ore-Isi (Urhoboland) and Benin, the article maps out how the coast’s lack of centralization, its complex settlement histories, and its underrepresentation in government and mainstream mission archives may be addressed by using multi-methods approaches and in-depth fieldwork. It emphasizes both the high mobility and heterogeneity of coastal communities and illustrates the diverse ways in which local leaders have mobilized a range of resources – including Islam, traditional practice, and especially Christianity – to ensure individual wellbeing and to affirm or re-shape local boundaries and hierarchies. This article argues that the study of the coast, like that of other borderlands, affirms that both mixing and the assertion of difference are constitutive of the political economy of the area.